Does a lower rate of unemployment indicate a good economic condition? - Ismail, Mazida; Roslan, Shashazrina (Universiti Teknologi MARA, Johor, 2025)
Among the common economic indicators for a country is their unemployment rate. The lesser the unemployment rate means more people in the country are working, thus indicating the country is in a good condition. Is this statement true?